2021
DOI: 10.1093/ecco-jcc/jjab076.680
|View full text |Cite
|
Sign up to set email alerts
|

P559 Efficacy of Ustekinumab in the treatment of patients with Crohn’s disease with failure to previous conventional or biologic therapy: an observational real-life study

Abstract: Background Ustekinumab (UST), a human anti-IL12/23p40 monoclonal antibody, was approved by FDA and EMA for the treatment of moderate to severe Crohn’s disease (CD). Whether UST is effective in inducing deep remission, including mucosal healing and transmural healing, in patients with CD in a real life setting is not completely clear. Methods The study was performed on 92 subjects (47 males; 45 females; mean age: 42 (17–78) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic remission is an important endpoint in clinical studies of the effectiveness of biologics. An Italian real-world study of ustekinumab in patients with CD reported clinical response and remission rates after 52 weeks of 51% and 35%, respectively [ 30 ]. However, the endoscopic response (45%) and mucosal healing (35%) rates were lower.…”
Section: Discussionmentioning
confidence: 99%
“…In most real-life studies, UST was used on anti-TNF-α failure or refractory patients [ 70 , 71 ]. In this specific clinical context, remission at 24 weeks and (when available) at 52 weeks ranged from 31% to 75% and 25% to 60%, respectively [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, mucosal healing (MH) and fecal calprotectin (FC) levels significantly improved under UST treatment [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , …”
Section: Resultsmentioning
confidence: 99%
“…Long-term data from the CERTIFI and UNITI-IM for CD, and UNIFI for UC, have proven the efficacy of UST for the induction and maintenance of remission in both IBDs, and the most favorable results were observed in naïve patients to biological drugs [ 21 , 22 , 23 , 24 , 25 ]. Numerous “real world” (RW) data that have emerged in recent years have confirmed the favorable clinical, endoscopic, and histological results in patients treated with UST, the safety of which has thus been strengthened [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The results of the first comparative study between UST and an anti-TNF-α have further supported this claim [ 60 ].…”
Section: Introductionmentioning
confidence: 99%